Tuning of CO gas sensing performance of spray pyrolyzed ZnO thin films by electron beam irradiation. (15th November 2020) - Ani, Aninamol; P, Poornesh; Nagaraja, K.K.; Kolesnikov, E.; Shchetinin, Igor V.; Antony, Albin; Kulkarni, Suresh D.; Sanjeev, Ganesh; Chandra Petwal, Vikash; Verma, Vijay Pal; Dwivedi, Jishnu
Abstract: Electron beam induced effects on the sensing performance of spray-coated ZnO thin films for carbon monoxide (CO) detection are reported. The optical transmittance of pristine film was around 80% and decreased upon e-beam treatment. XRD studies confirmed the hexagonal wurtzite structure of ZnO. Carbon monoxide (CO) sensing measurements performed at 300 °C revealed that irradiated ZnO films exhibited enhanced response and recovery time compared to pristine film. The 5 kGy irradiated film displayed improved sensing performance with respect to response and recovery time towards the CO concentrations tested. It showed a quick response time of 43 s and a recovery time of 77 s towards the lowest detected CO gas limit of 2 ppm. The response time of 10 kGy irradiated film was 5 s towards 2 ppm. The 5 kGy irradiated ZnO sensor exhibited an excellent response of 1.39 and 2.63 towards 2 ppm and 5 ppm of CO gas respectively. The observed enhancement in both response and recovery times as well as response of the sensor is ascribed to the oxygen vacancies present in the film which is evident from the photoluminescence studies and also due to large number of grain boundaries. Graphical abstract: Image 1 Highlights: Electron beam irradiated ZnO thin film exhibited improved response and recovery times to low concentration (2 ppm) of CO gas. Increased oxygen vacancies due to irradiation act as a potential enhancer. Enhanced sensor response was displayed by 5 kGy irradiated ZnO thin film.